Theories, Practices, and Research in Conflict Resolution and Low-Intensity Conflicts:: The Kurdish Conflict in Turkey - Ozcelik, Sezai (Journal of Conflict Studies, 2006)
ABSTRACT This article analyzes the Kurdish conflict in terms of the theories and practices of conflict resolution. The low-intensity conflict in Turkey is used for the application of conflict resolution theories, namely basic human needs (BHNs), dissonance (relative deprivation), realist, psychodynamic, and chaos theories to explain and understand deep-rooted and protracted intra-state conflicts. Before analyzing the conflict with an interdisciplinary approach and different theories, the historical background is presented. The psychodynamic approach (externalization, projection, chosen traumas, dehumanization, the egoism of victimization, the need for the enemies and allies, and the ethnic identity formation) are necessary to explain the Kurdish question in Turkey in the post-11 September world order. With the help of conflict resolution tools, the author analyzes the use of interactive problem-solving workshop (PSWs) to find a common ground between Turks and Kurds. The article concludes that the conflict should be explained and understood not only within the context of terrorism and economic backwardness, but also identity and basic human security needs of the conflicting parties. It also requires using both military and conflict resolution tools.